Developmental Course of Attention Deficit Hyperactivity Disorder and its Predictors - Cherkasova, Mariya (Canadian Academy of Child and Adolescent Psychiatry, 2013)
OBJECTIVE: To outline the key features of the developmental progression of ADHD and to consider the most prominent influences on its developmental course and outcomes. METHODS: This is a selective review focusing primarily on prospective follow-up studies. Relevant publications were selected by searching the MEDLINE and PubMed databases using keywords: ADHD, development, preschool, adolescent, adult, follow up, outcome, long-term, predictors, and treatment. Reference lists of the resulting articles were then reviewed for additional publications. RESULTS: Presentation of ADHD and associated impairments evolve across development, as do outcome predictors. In early development, in addition to genetics, some forms of prenatal adversity increase the risk for ADHD. In preschool years, symptom severity, cognitive function, and family factors become significant predictors of school age outcomes. These continue to predict long-term outcomes in school aged children, and comorbidity emerges as another significant long-term outcome predictor at this stage. CONCLUSIONS: Presentation of ADHD and risk factors for later adversity evolve across development, which calls for developmentally-informed clinical practices.